Culture university and culture policy in Venezuela. Agreements and disagreements (Ágora de Heterodoxias, 2015)
The processes of social change tend to have two almost immediate repercussions: changes in political culture and in the nature of education. Venezuela in the context of what has been called the Bolivarian Revolution is a clear example of this reality, especially when trying to locate the political system and the university system in the same analytic dimension. This is how, since the 1990s, this situation put the university problem in a space adjacent to the processes of political transformation in Venezuela. Thus, in the UNELLEZ, institutional and curricular evaluation, although born in the heat of domestic concerns, is fortified, encouraged and in many cases is due to the dynamic imposed by the set of changes that occurred and are about to occur in the venezuelans political system and thought. This reflection has tried to contextualize this complex bundle of dialectical relations in order to put on the table the political-ideological directionality that the venezuelan universities would be taking, once permeated with The aroma of the so-called political revolution that the country is experiencing. The interesting thing is the different responses which can produce this situation in the university actors, assuming that their diversity and their undisputed critical view would prevent them from staying isolated from the process.  Either way, the analysis allowed corroborating the need for the university institution to be renewed and also to make evident that such innovative efforts have strongly been driven by the evaluation processes, the social demand and the socio-political dynamics.
Keywords: political culture; university culture; political change; university change